Qudratic Equation-

Algebra Level 3

If both the roots of a quadratic equation a x 2 + b x + c = 0 ax^2 + bx + c = 0 differ by a real number m m then find out the value of the discriminant of the quadratic equation.

m(a)^2 (m)^2a (ma)^2 ma

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Samarth Sangam
Oct 11, 2014

Q u a d r a t i c e q u a t i o n a x 2 + b x + c = 0 D i s c r i m i n a n t D = b 2 4 a c L e t i t s r o o t s b e x 1 a n d x 2 t h e n x 1 + x 2 = b a ; x 1 x 2 = c a x 1 x 2 = m ( x 1 x 2 ) 2 = ( x 1 + x 2 ) 2 4 x 1 x 2 m 2 = b 2 a 2 4 c a ( m a ) 2 = b 2 4 a c Quadratic\quad equation\Longrightarrow a{ x }^{ 2 }+bx+c=0\\ Discriminant\quad D={ b }^{ 2 }-4ac\\ Let\quad its\quad roots\quad be\quad { x }_{ 1 }\quad and\quad { x }_{ 2 }\quad \\ then\quad { x }_{ 1 }+{ x }_{ 2 }=-\frac { b }{ a } \quad ;\quad { x }_{ 1 }{ x }_{ 2 }=\frac { c }{ a } \\ { x }_{ 1 }-{ x }_{ 2 }=m\\ { \left( { x }_{ 1 }-{ { x }_{ 2 } } \right) }^{ 2 }\quad ={ \left( { x }_{ 1 }+{ { x }_{ 2 } } \right) }^{ 2 }-4{ x }_{ 1 }{ x }_{ 2 }\\ \quad \quad \quad \quad { m }^{ 2 }=\frac { { b }^{ 2 } }{ { a }^{ 2 } } -4\frac { c }{ a } \\ \quad \qquad \quad { (ma) }^{ 2 }={ b }^{ 2 }-4ac

nice method!!

Krishna Ramesh - 6 years, 7 months ago

R o o t s o f a x 2 + b x + c = 0 , b y q u a d r a t i c f o r m u l a = b ± D 2 a , w h e r e D i s t h e d i s c r i m i n a n t . A c c . t o q u e s t i o n , r o o t s d i f f e r b y m i . e . b + D 2 a m = b D 2 a b + D 2 a m 2 a = b D 2 a C a n c e l l i n g b a n d 2 a , w e a r e l e f t w i t h : D 2 a m = D 2 D = 2 a m C a n c e l l i n g 2 a n d s q u a r i n g : D = ( a m ) 2 Roots\quad of\quad a{ x }^{ 2 }+bx+c=0,\quad by\quad quadratic\quad formula\\ =\quad \frac { -b\pm \sqrt { D } }{ 2a } ,\quad where\quad D\quad is\quad the\quad discriminant.\\ Acc.\quad to\quad question,\quad roots\quad differ\quad by\quad 'm'\quad i.e.\\ \frac { -b+\sqrt { D } }{ 2a } \quad -\quad m\quad =\quad \frac { -b-\sqrt { D } }{ 2a } \\ \frac { -b+\sqrt { D } -2am }{ 2a } \quad =\quad \frac { -b-\sqrt { D } }{ 2a } \\ Cancelling\quad '-b'\quad and\quad '2a',\quad we\quad are\quad left\quad with:\\ \sqrt { D } -2am\quad =\quad -\sqrt { D } \\ 2\sqrt { D } \quad =\quad 2am\\ Cancelling\quad '2'\quad and\quad squaring:\\ D={ (am) }^{ 2 }

CHEERS!!:):)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...